TINJAUAN YURIDIS PERSELISIHAN PEMUTUSAN HUBUNGAN KERJA TIDAK SESUAI DENGAN PERATURAN ( STUDI PUTUSAN PERKARA PHI NOMOR 272/PDT.SUS-PHI/2018/PN.MDN ) - Nadapdap, Gindo (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
One of the problems that often arises in employment relations is the problem of layoffs, where workers are always the weak party when faced with employers who are parties who have strength, as parties who are always considered weak, it is not uncommon for workers to always experience injustice when faced with company interests. The purpose of this study is to determine the obligations of Sari Mutiara Medan General Hospital (Defendant) towards the rights of workers / SUTRISNI (Plaintiff) based on a work mutation letter dated June 14, 2018 Number: 837 / I.2 / RSU-SM / VI / 2018 without clear procedural and legal basis and does not pay attention to objectivity / fulfill a sense of justice and know the legal consequences of the decision Number 272 / Pdt.Sus-PHI / 2021 / PN.Mdn concerning termination of employment of the parties (Employers and Workers). The type of research used in this study uses normative juridical research methods. The problem approach used in this study includes the legal approach and the case approach. The results of the study show that layoffs are employment relationships due to certain things that result in the end of rights and obligations between workers and companies. This can happen due to resignation, dismissal by the company or expiration of the contract. In the world of work, especially for workers, it cannot be separated from the word layoff and can come at any time. But companies laying off workers must have their own reasons, therefore the Manpower Law was created. And more precisely in Article 150 – Article 172, it is regulated about the reasons for layoffs. In Decision Number 272 / Pdt.Sus-PHI / 2018 / Pn.Mdn that I took, contains a case about